Management Of Stravi Arsha With Nagkesar And Mishri - Sharma, Sheetal (International Research Journal of Ayurveda & Yoga, 2020)
The greed of humans to use everything in excess is a cause of disease. Every disease has got its special etiology with which is creates signs and symptoms. Stravi and Suksha; are two types of Arsha. Stravi Arsh is Pitta and Rakta dominant. Bleeding per rectal is a main symptom of the disease; when left untreated may cause an emergency condition. Arsha is a result of improper dietary habits as well as life style. Stravi Arsha is bleeding pile in modern science. Different treatment modalities are available such as injection therapy, Rubber band ligation, operative treatment but the risk of recurrence and infection in the wound after operation is high. Stravi Arsha or bleeding piles which sometimes ask for immediate treatment can be cured with conservative treatment in Ayurveda. Ayurveda provides cure and prevent recurrences in early stage of diseases. The present study is carried out to see the efficacy of Nagkesar churna and Mishri as a conservative treatment in Ayurveda.